Production of Lactic Acid by lactobacilli using Legume Flours - Gandhi, Prachi (Iraqi Journal of Science, 2023)
Due to their high nutritional value, richness in carbohydrates and good source of protein, legumes are considered essential for human diet. Legumes flours were used as fermentable material for lactic acid production. Hence, previously isolated lactobacilli strains were used in this study. The strains showed strong microbial growth and their survival in glucose-containing MRS medium and were described using a modified Gompertz equation. Lactobacilli exhibited the shortest latency phase in MRS-glucose medium. While the highest lactic acid produced was 15.40g/l by Lpb. pentosus U1 isolate after 48hours. Furthermore, these strains were evaluated in flours samples for acidification capacity. The results showed a decrease in pH values after 12hours of fermentation, indicating the fastest acidification with maximum lactic acid generation of 31.66, 25.33, 31.00 and 31.66g/l for black gram flour by Lpb. plantarum M1, Lpb. pentosus U1, Lpb. plantarum VIP1 and Lev. brevis TIP1 isolates. Black gram flour was considered the best among the used substrates for enhancing lactic acid production. Overall, this study can be termed as a preliminary step for fermentation using the desired organism in preparing legume-based food at the industrial level and benefiting consumers.